Antibacterial antiadhesion membranes from silver‐nanoparticle‐doped electrospun poly(L‐lactide) nanofibers. Issue 6 (28th February 2013) - Liu, Shen; Liu, Shenghe; Liu, Xudong; Zhao, Jingwen; Cui, Wenguo; Fan, Cunyi
Abstract Electrospun fibrous membranes have been used frequently in biomedical applications, but their simultaneous use as antibacterial agents and in the prevention of cell adhesion on repaired tendons after injury has not been investigated. In this study, silver‐nanoparticle (SN)‐loaded poly(L‐lactide) (PLLA) fibrous membranes were prepared by the electrospinning of SNs into PLLA fibers. Micrograph results showed that these membranes were composed of electrospun fibers and that the fibers were incorporated with SNs. From the results of X‐ray diffraction and thermogravimetry, we concluded that the SNs were physically mixed into the fibers at the desired content. The mechanical properties were not significantly changed. The preliminary antibacterial effects on Staphylococcus epidermidis and Staphylococcus aureus and the synergistic antiproliferative effects of the SN‐loaded PLLA fibrous membranes were observed. Taken together, these results demonstrate that SNs can be directly loaded onto a biodegradable PLLA fibrous membrane via electrospinning to achieve proper material properties with preliminary potential as antibacterial antiadhesion barriers for tendon injury. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013